Comparison of predicted postoperative forced expiratory volume in the first second (FEV1) using lung perfusion scintigraphy with observed forced expiratory volume in the first second (FEV1) post lung resection - Boon Mathew; Sudipta Nag; Archi Agrawal; Priya Ranganathan; Nilendu Purandare; Sneha Shah; Ameya Puranik; Venkatesh Rangarajan (World Journal of Nuclear Medicine)
Lung perfusion scintigraphy is done as a part of preoperative evaluation in lung cancer patients for the prediction of postoperative forced expiratory volume in the first second (FEV1). This study was performed to see the accuracy of prediction of postoperative FEV1 by perfusion scintigraphy for patients undergoing lobectomy/pneumonectomy by comparing it with actual postoperative FEV1 obtained by spirometry 4–6 months after surgery. We retrospectively reviewed 50 surgically resected lung cancer patients who underwent preoperative spirometry, lung perfusion study, and postoperative spirometry. Pearson's correlation coefficient was used to evaluate the relationship between predicted postoperative FEV1 (PPO FEV1) by lung perfusion scintigraphy and postoperative actual FEV1 measured by spirometry. Agreement between the two methods was analyzed with Bland–Altman method. The correlation between the PPO FEV1 and actual postoperative FEV1 was statistically significant (r = 0.847, P = 0.000). The correlation was better for pneumonectomy compared to lobectomy (r = 0.930 [P = 0.000] vs. 0.792 [P = 0.000]). The agreement analysis showed a mean difference of −0.0558 with a standard deviation (SD) of 0.284. The limits of agreement vary over a wide range from −−0.625 to 0.513 L (mean ± 2 SD) for the entire group. For pneumonectomy, the mean difference was −0.0121 and SD 0.169 with limits of agreement varying between −0.30 L and 0.30 L. For lobectomy, the mean difference was −0.0826 and SD 0.336 with limits of agreement varying between −0.755 L and 0.590 L. Postoperative FEV1 predicted using lung perfusion scintigraphy shows good correlation with actual postoperative FEV1 and shows reasonably good agreement in patients undergoing pneumonectomy. The limits of agreement appear to be clinically unacceptable in patients undergoing lobectomy, where single-photon emission computed tomography (SPECT) or SPECT/CT techniques may improve prediction.